Internal Control Practices for Cash and Receivable Management: Praktik Pengendalian Internal untuk Pengelolaan Kas dan Piutang - Hadiah Fitriyah; Selvia Umi Muhlishoh (Indonesian Journal of Law and Economics Review, 2025)
General Background Cash and trade receivables represent critical current assets that determine organizational liquidity and financial stability. Specific Background Many organizations experience administrative weaknesses that lead to delayed collections and uncollectible accounts due to inadequate internal control procedures. Knowledge Gap Limited empirical evaluations describe how internal control systems for cash receipts and receivables are implemented and assessed in specific operational contexts. Aims This study aims to evaluate the procedures, documentation, and monitoring mechanisms applied in managing cash and receivables and to identify strengths and weaknesses within the existing system. Results Using a descriptive qualitative approach through observation, interviews, and document analysis, the findings indicate that basic controls such as authorization, recording, and segregation of duties are implemented, yet several weaknesses remain, including incomplete documentation and inconsistent supervision that may increase collection risk. Novelty The study provides a case-based evaluation combining procedural review with practical accounting perspectives in daily financial operations. Implications The results suggest the need for structured documentation, consistent monitoring, and standardized control procedures to support reliable cash flow and receivable management. Keywords: Internal Control, Cash Management, Accounts Receivable, Financial Procedures, Accounting System Key Findings Highlights: Duties separation applied but monitoring not consistent Collection procedures rely on manual documentation Risk of delayed settlement remains observable